Climate-Resilient Dairy Cattle Production: Applications of Genomic Tools and Statistical Models - Silpa, Mullakkalparambil Velayudhan; König, Sven; Sejian, Veerasamy; Malik, Pradeep Kumar; Nair, Mini Ravi Reshma; Fonseca, Vinicius F. C.; Maia, Alex Sandro Campos; Bhatta, Raghavendra (Frontiers in Veterinary Science, 2021)
The current changing climate trend poses a threat to the productive efficacy and welfare of livestock across the globe. This review is an attempt to synthesize information pertaining to the applications of various genomic tools and statistical models that are available to identify climate resilient dairy cows. The different functional and economical traits which govern the milk production play a significant role in determining the cost of milk production. Thus, identification of these traits may revolutionize the breeding programs to develop climate resilient dairy cattle. Moreover the genotype-environment interaction also influences the performance of dairy cattle especially during challenging situation. The recent advancement in molecular biology have led to development of few biotechnological tools and statistical models like next generation sequencing (NGS)microarray technology, whole transcriptome analysis and genome wide association studies (GWAS) which can be used to quantify the molecular mechanisms which controls the climate resilience capacity of dairy cows. Among these, the most preferred option for the researchers around the globe was GWAS as this approach jointly takes into account all the genotype, phenotype and pedigree information of an organism. Further, selection signatures can also help to demarcate functionally important regions in the genome which can be used to detect potential loci and candidate genes that have undergone positive selection in complex milk production traits of dairy cattle. These identified biomarkers can be incorporated in the existing breeding policies using genomic selection to develop climate resilient dairy cattle.